Pre-hospital Utility of Rapid Stroke evaluation Using In-ambulance Telemedicine (PURSUIT): A Pilot Feasibility Study - Wu, Tzu-Ching (2014)
BACKGROUND AND PURPOSE: : Pre-hospital evaluation using telemedicine (TM) may accelerate acute stroke treatment with tissue plasminogen activator (t-PA). We explored the feasibility and reliability of using TM in the field and ambulance to help evaluate acute stroke patients. METHODS: : Ten unique, scripted stroke scenarios, each conducted four times, were portrayed by trained actors retrieved and transported by Houston Fire Department emergency medical technicians (EMT) to our stroke center. The vascular neurologists (VN) performed remote assessments in real-time, obtaining clinical data points and NIH Stroke-Scale (NIHSS) using the In-Touch RP-Xpress TM device. Each scripted scenario was recorded for a subsequent evaluation by a second blinded VN. Study feasibility was defined by the ability to conduct 80% of the sessions without major technological limitations. Reliability of video interpretation was defined by a 90% concordance between the data derived during the real-time sessions and the scripted scenarios. RESULTS: In 34/40 (85%) scenarios, the teleconsultation was conducted without major technical complication. The absolute agreement for intra-class-correlation (ICC) was 0.997 (95% CI: 0.992-0.999) for the NIHSS obtained during the real-time sessions and 0.993 (95% CI: 0.975-0.999) for the recorded sessions. Inter-rater agreement using κ-statistics showed that for live-raters, 10/15 items on the NIHSS showed excellent agreement, and 5/15 showed moderate agreement. Matching of real-time assessments occurred for 88% (30/34) of NIHSS scores by ±2 points, and 96% of the clinical information. CONCLUSIONS: Mobile TM is reliable and feasible in assessing actors simulating acute stroke in the pre-hospital setting.